Taʾtsīr istiʿāb al-mufradāt al-ʿArabiyyah ʿalā mahārat al-talāmīdh fī al-kalām al-ʿArabī li-talāmīdh al-ṣaff al-tāsiʿ fī Madrasa Kārisma Dār al-Salām al-Mutawassiṭah al-Islāmiyyah al-Mutakāmilah Karawang - Zakiyah; Prasetiadi, Yan Septian (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2022)
The effect of comprehension of Arabic vocabulary on students' skill in Arabic speaking. The purpose of this research is to know the comprehension of Arabic vocabulary and the students' ability in Arabic speech, and the effect of comprehension of Arabic vocabulary on students' skill in Arabic speech. Vocabulary is the means of carrying meaning as well as in another time as a means of thinking. Because the speaker can think and then express what came to his mind and thought in the words of what he wants. Speaking skill is an important tool for building understanding and positive communication, as language becomes a means to do so. And that in the Arabic language is an important way as well. Speech was someone's skill in performing communication using the Arabic language as his medium. This research is a quantitative research concerned with the two variables. The type of this research is case research. The researchers used both desk and field sources to obtain data in writing this paper. The method of data collection has done by distributing the questionnaire, testing, observation and documentation method. I have done the data analysis method using Microsoft Excel to collect the data first and then using the spss (statistical package of social science) program. for statistical calculation activities. The fact that the assimilation of Arabic vocabulary was carried out with excellent publication. Because the results of data analysis indicate that the minimum value obtained is 83 and the highest value is 100. The average Arabic vocabulary comprehension was 94 or 94%. The fact that the students’ skill in Arabic speaking was implemented with excellent publication because the results of data analysis indicate that the minimum value obtained is 85 and the highest value is 100. The average students’ skill in Arabic speaking is 94 or 94%. And the fact that the effect of comprehension of Arabic vocabulary on the students’ skill in Arabic speaking indicates the Rsquare coefficient of 0.404. This indicates the understanding that the y variable is affected by the sigmoid variable by an amount of 40%. The rest is affected by other factors.